Aves da baixada de Guaratiba, Rio de Janeiro, Brasil, 22º 50'S/43º 36'W - Ventura, Pedro Ernesto Correia (1985)
The author presents a list of birds from the lowlands of Guaratiba 22° 50'S/43° 36'W. an area to the west of the Municipio of Rio de Janeiro, formerly called Guanabara State (SICK & PABST 1968), observed in the period 1980 – 1983. Besides the identification of the species and its distribution in Orders and families, there is also some discusdion concerning the movements of birds in the region permitting its division in resident, migrant or visiting species. Included are some facts about habitat. reproduction. feeding and predation and behavior in the species involved and also discussion of some aspects involving changes in relation to water level. Some comparisons were made with data of other authors who developed similar works in similar areas of the State. 130 species of birds were observed, belonging to seventeen Orders and forty Families. Twelve are new occurences to the Municipio of Rio de Janeiro and six of these are also new for the whole State. Sixteen others are considered rare, uncommon or were only seen recently there.